Blue and Red Light Color Combinations Can Enhance Certain Aspects of Digestive and Anabolic Performance in Juvenile Steelhead Trout Oncorhynchus mykiss - Chen, Xueweijie; Zhou, Yangen; Huang, Jinze; An, Dong; Li, Li; Dong, Yunwei; Gao, Qinfeng; Dong, Shuanglin (Frontiers in Marine Science, 2022)
The light spectrum varies with the altitude of the sun and shows different light colors in clear water. In this study, we aimed to investigate the response of juvenile steelhead trout Oncorhynchus mykiss (34.67 ± 2.69 g initial weight) under different light color conditions. The effects of different blue and red light combinations on plasma biochemical parameters, digestive enzyme activity, and RNA/DNA ratio were assessed in trout over 16 weeks. Six treatments were randomly assigned to 24 tanks with four replicates per treatment: a constant light intensity of 150 lx: 12 h white light then 12 h dark (12W); 12 h blue light then 12 h dark (12B); 12 h red light then 12 h dark (12R); 1.5 h blue light, 9 h red light, 1.5 h blue light, then 12 h dark (3B9R); 3 h blue light, 6 h red light, 3 h blue light, then 12 h dark (6B6R); and 12 h of both blue and red light then 12 h dark (T12BR). Fish exposed to the 3B9R light environment showed significantly increased plasma levels of total protein (TP), enhanced activities of midgut lipase, trypsin, and gastric lipase; and increased RNA content in the liver and muscle tissue to promote protein synthesis efficiency, thereby improving digestive and anabolic performance compared to fish in the other treatments. This indicates that steelhead trout have adapted well to such variable light conditions during long-term evolution. In contrast, trout exposed to the 6B6R light environment showed significant reductions in plasma glucose, TP, and triglyceride levels, decreased activity of gastrointestinal digestive enzymes, and reduced protein synthesis capacity in the muscle and liver, resulting in weakened digestive and anabolic performance. Furthermore, despite the high RNA content and RNA/DNA ratio in fish exposed to a 12R light environment, relatively high plasma cholesterol and triglycerides levels were observed, which might indicate oxidative stress. Therefore, this light is not considered suitable for long-term cultivation. In conclusion, the 3B9R treatment was the optimal light condition tested and can be used to improve the digestive and anabolic performance of steelhead trout.